1994
DOI: 10.1164/ajrccm.150.4.7522854
|View full text |Cite
|
Sign up to set email alerts
|

Antigen-specific stimulation of histamine releasing factors in diisocyanate-induced occupational asthma.

Abstract: Diisocyanate-induced asthma differs from occupational asthma (OA) caused by protein allergens in that specific IgE antibody responses are rarely identified. To investigate the immunopathogenesis of diisocyanate asthma, diisocyanate-exposed workers were evaluated for in vitro production of antigen-specific mononuclear cell-derived histamine releasing factor (HRF). The mean HRF response to diisocyanate-HSA antigens was significantly greater in patients with OA than in diisocyanate-exposed asymptomatic subjects (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

1996
1996
2006
2006

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 0 publications
2
6
0
Order By: Relevance
“…Several previous studies have found no association between elevated levels of specific IgG antibodies to the MDI-HSA antigen, and confirmed OA [ZammitTabona et al, 1983;Tse et al, 1985;Herd and Bernstein, 1994;Lummus et al, 1996]. In this investigation, three workers with an increased IgG antibody level were symptomatic, three were asymptomatic, and none had symptoms suggestive of hypersensitivity pneumonitis.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…Several previous studies have found no association between elevated levels of specific IgG antibodies to the MDI-HSA antigen, and confirmed OA [ZammitTabona et al, 1983;Tse et al, 1985;Herd and Bernstein, 1994;Lummus et al, 1996]. In this investigation, three workers with an increased IgG antibody level were symptomatic, three were asymptomatic, and none had symptoms suggestive of hypersensitivity pneumonitis.…”
Section: Discussionsupporting
confidence: 79%
“…Considerable evidence exists indicating that workers with IgG or IgE antibodies specific for one diisocyanate-HSA conjugate exhibit cross-reactivity to antigens prepared with other diisocyanates, to which there have been no workplace exposures [O'Brien et al, 1979;Baur, 1983;Baur and Fruhman, 1981;Malo et al, 1983]. A recent study of workers with confirmed diisocyanate-induced asthma found that diisocyanate-HSA antigens stimulated the production of histamine releasing factor (HRF) by the peripheral blood mononuclear cells [Herd and Bernstein, 1994]. The presence of IgE or IgG antibodies did not correlate with HRF activity, nor with a diagnosis of OA.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, when haptenspecific proliferative response is present, its magnitude is significantly smaller than that induced by common inhalant allergens [108]. In vitro experiments have also reported that PBMCs of workers with diisocyanate-induced OA demonstrate a hapten-specific production of histamine-releasing factor [112,113] and the release of monocyte chemoattractant protein-1, interleukin (IL)-8, tumour necrosis factor (TNF)-a, and interferon (IFN)-c [114]. However, it remains to be established whether LMW agents are capable of inducing a direct, IgE-independent, hapten-specific activation of PBMCs.…”
Section: Cell-mediated Immunitymentioning
confidence: 99%
“…Positive skin-prick tests, specific IgE, and IgG have been shown to be present mainly in atopic subjects sensitized to high-molecular-weight sensitizing agents (29), but also in some subjects sensitized to low-molecular-weight agents (e.g., anhydrides, platinum salts, nickel, plicatic acid, and isocyanates) (30)(31)(32)(33)(34). In subjects with occupational asthma induced by both high-and low-molecular-weight compounds, specific immunoglobulins (IgE, IgG) may be found (30)(31)(32)(33)(34). Skin tests and specific antibodies may, therefore, be helpful in the diagnosis of occupational asthma due to high-molecular-weight compounds (35).…”
Section: Antibody-mediated Hypersensitivitymentioning
confidence: 99%